Effect of pre-emptive intravenous paracetamol, magnesium sulfate, and lignocaine on hemodynamic variables during perioperative period in pre-eclampsia patients scheduled for lower segment cesarean section under general anesthesia: A prospective randomized study - Dilip Kothari; Anjali Bansal; Seethal Ann Sunny (Asian Journal of Medical Sciences, 2022)
Background: Hemodynamic alterations during general anesthesia with endotracheal intubation are due to stimulation of the sympathetic nervous system and catecholamine release. Therefore, it is important to attenuate these responses in pre-eclampsia patients who are already under stress. Aims and Objectives: The present study aimed to evaluate the combined efficacy of paracetamol, magnesium sulfate, and lignocaine in attenuating hemodynamic responses during intubation and perioperative period. Materials and Methods: Eighty ASA II pre-eclampsia patients were randomly divided into two groups. Group PLM received intravenous infusion of paracetamol (1 g) and magnesium sulfate (30 mg/kg) in 100 ml normal saline and IV bolus Inj. lignocaine (1.5 mg/kg) 15 min before induction. Group C received only IV infusion of 100 ml normal saline. Pulse rate (PR), blood pressure (BP), and oxygen saturation were measured at various time intervals up to 40 min of delivery of baby and in up to 240 min in post-operative period. Post-operative visual analog score (VAS) and the time for first rescue analgesia (TRA I) were recorded. Results: Demographic and baseline hemodynamic parameters were comparable in both groups (P>0.05). Changes in PR and BP during laryngoscopy, intubation, and perioperative period were significantly lesser in Group PLM as compared to Group C (P<0.05). The post-operative VAS score was significantly lower whereas TRA I was significantly longer in Group PLM than in Group C at all measuring times (P<0.05). Conclusion: Combination of paracetamol, magnesium sulfate, and lignocaine attenuates hemodynamic responses during laryngoscopy, intubation, and perioperative period along with prolonged post-operative analgesia in cesarean section under general anesthesia in pre-eclampsia patients.